Uvajanje teme onesnaženost zraka v osnovne šole z izkustvenim učenjem – predstavitev primera - Benčina, Marjeta (Sodobna pedagogika, 2025)
Air pollution is the most important public health problem leading to increased mortality and morbidity in the population. Air pollutants differ in their origin and chemical composition. Particulate matter is a major air pollutant, with black carbon being an important component. Black carbon is produced by the incomplete combustion of fossil fuels and biomass in transport and household heating. In Slovenia, the main sources are transport, energy production, and individual heating systems. Due to their small size, these particles can penetrate deep into the respiratory tract and cause a variety of illnesses with prolonged exposure. Children, as a particularly vulnerable group, are even exposed to pollutants at school. As users of space, they can work with teachers to propose measures to improve air quality around the school and in the community, while municipalities and the state are expected to implement measures to protect the health of the people for whom they are responsible. As users of space, together with the teachers, they can propose measures to improve the air quality around the school and in the community, while the municipalities and the state are expected to implement measures to protect the health of the people for whom they are responsible. Through workshops, soot measurements in selected primary schools and local initiatives, we have shown that experiential, research-based project learning is useful to sensitise students, teachers, schools and the local community to take action to reduce concentrations of harmful air pollutants. We have collected suggestions for introducing content and activities on the topic of air pollution in science and technology in grade 5 and suggest how the topic can be integrated into other subjects.
Keywords: active citizenship; air pollution; aktivno državljanstvo; black carbon; črni ogljik; experiential learning; influence on health; izkustveno učenje; local initiatives; lokalne pobude; onesnaženost zraka; raziskovalno delo; research work; vpliv na zdravje